p53 and its role in the ovarian surface epithelium. A review (2008)
The ovarian surface epithelium (OSE) is a single layer of cells subject to a high rate of turnover at he site of follicular rupture at ovulation and this results in a higher risk of malignant cell transformation. Findings like cancer derived from OSE, that accounts for approximately 90% of all human ovarian malignancies and the frequent mutations of the p53 gen in most of them, are the basis for reviewing OSE structure and histogenesis related to p53, as well as some aspects associated with p53 stabilization and regulation, its involvement in key events like cell cycle arrest, induction of apoptosis, etiology and pathogenesis of epithelial ovarian cancer. Finally, this review takes into account recent farmacogenetics advances in order to use p53 as a target. in the therapy against cancer.